2019
DOI: 10.1002/lary.28144
|View full text |Cite
|
Sign up to set email alerts
|

Is robotic surgery an option for early T‐stage laryngeal cancer? Early nationwide results

Abstract: Objectives/Hypothesis: To characterize patients undergoing laryngeal transoral robotic surgery (TORS) and compare to open partial surgery and transoral laser microsurgery (TLM) in achieving negative margins, requiring adjuvant radiation, and overall survival. Study Design: Retrospective database analysis. Methods: Early-stage (T1/2) laryngeal squamous cell carcinoma patients from the National Cancer Database. Univariable and multivariable logistic and Cox regressions were used to identify predictors. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
0
14
0
5
Order By: Relevance
“…In the treatment of early staged (T1–T2) (supra)glottic carcinoma radio-chemotherapy and surgical treatment, especially TLM, are considered as standard treatments, which offer similar (good) results in oncological outcome [ 11 ]. In one of the few directly comparative retrospective databases analysis studies, Hanna et al showed that also transoral robotic surgery (TORS) can achieve competitive oncological results, since there was no observed difference in margin status and necessitating adjuvant radiation compared to TLM [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the treatment of early staged (T1–T2) (supra)glottic carcinoma radio-chemotherapy and surgical treatment, especially TLM, are considered as standard treatments, which offer similar (good) results in oncological outcome [ 11 ]. In one of the few directly comparative retrospective databases analysis studies, Hanna et al showed that also transoral robotic surgery (TORS) can achieve competitive oncological results, since there was no observed difference in margin status and necessitating adjuvant radiation compared to TLM [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A further evaluation was subsequently carried out by Hanna et al to compare negative margins and overall survival rates between patients undergoing TORS, TLM, and conventional trans-oral surgery. 15 This retrospective analysis of 1780 patients in the US National Cancer Database with T1 and 2 laryngeal squamous cell carcinoma found that TORS patients had a lower rate of positive margins than open surgery (when compared to open surgery [TORS: HR 1.56, p = 0.05], [TLM: HR 1.52, p = 0.05]). The highest 5-year overall survival was in the TORS cohort.…”
Section: Importance Of Disease-free Marginsmentioning
confidence: 99%
“…Am häufigsten kommt die TORS außerhalb des Oropharynx bei der Resektion von supraglottischen Larynxkarzinomen zum Einsatz [200]. Eine aktuelle Meta-Analyse von Lechien und Co-Autoren an 422 Patienten mit supraglottischen Larynxkarzinomen zeigt gute onkologische Ergebnisse nach TORS mit dem da Vinci-System mit 5-Jahres rezidivfreien Überlebensraten von über 90 % [201].…”
Section: Supraglottische Und Glottische Larynxkarziomeunclassified
“…Outside the oropharynx, TORS is most commonly used for the resection of supraglottic laryngeal carcinomas [200]. A recent metaanalysis by Lechien and co-authors on 422 patients with supraglottic laryngeal carcinomas showed good oncologic outcomes after TORS with the da Vinci system with 5-year recurrence-free survival rates of more than 90 % [201].…”
Section: Supraglottic and Glottic Laryngeal Carcinomasmentioning
confidence: 99%
See 1 more Smart Citation